Perancangan Website Upload Izin Usaha di Dinas Penanaman Modal dan Pelayan Terpadu Satu Pintu - Khoirul Huda Dwi Putra; Ikhsan Nuttakwa Takbirata Ihram Nabawi; Muhammad Rahman Hidayat; Muhammad Rayhan Elfansyah; Muhammad Farhat Jundullah; Arbansyah Arbansyah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The central government created an electronic business-oriented service system to overcome the problem of slow licensing services in various regions in Indonesia as well as improving public services in processing business permits. The problem currently being experienced by the East Kalimantan Province DPMPTSP is how to arrange permits from business actors who want to upload files and check if there is an error in uploading the business permit. The aim of this research is to create a website that can be used. business actors to upload a permit to carry out the desired business. The process of creating a website involves several tools and code languages ​​that are used, namely: php, xampp, phpmyadmin, mysql, database, website. The result is a website with various features, such as login page, dashboard, profile, user management, upload files, supporting files, and scan files. From the results of the discussion and data obtained, we can conclude that students who undertake internships directly in the world of work can gain more knowledge, understanding and knowledge.